Transmission orientation imaging of copper thin films on polyimide substrates intended for flexible electronics. (September 2017) - Lee, So-Yeon; Guim, Hwan-Uk; Kim, Dong-Ik; Joo, Young-Chang; Shim, Cheol-Hwee; Ahn, Jae-Pyoung; Choi, In-Suk; Abbasi, Majid
Abstract: Nanostructure of cupper thin film on polyimide flexible substrate is revealed by novel orientation imaging techniques. Copper and polyimide thicknesses play critical roles on what technique is successful in acquiring diffraction patterns while avoiding electron beam damage and blistering. Conventional electron backscattered diffraction as well as emerging higher resolution transmission orientation imaging were employed to resolve the grain structure. Spatial resolution is compared in terms of minimum detectable twin width. Experiments and simulations indicate that polyimide thicknesses below 1000 nm allow the electrons to scape; resulting in acceptable reflective or transmission patterns and lack of blistering. Graphical abstract: